2010
DOI: 10.1590/1808-1657v77p0572010
|View full text |Cite
|
Sign up to set email alerts
|

Efeito Do Nim (Azadirachta Indica) Na Mosca-Das-Frutas Ceratiti. Capitata (Diptera: Tephritidae) E Seu Parasitoide Diachasmimorpha Longicaudata (Hymenoptera: Braconidae)

Abstract: RESUMO Este trabalho teve como objetivo avaliar a ação do inseticida botânico nim em larvas de Ceratitis capitata, bem como no parasitismo destas larvas por Diachasmimorpha longicaudata. Para tanto, larvas de 3o ínstar de C. capitata foram mergulhadas por 30 segundos em soluções contendo as concentrações de 0,5%, 1% e 1,5% de um produto comercial à base de óleo de nim a 0,37% (3.686 ppm), além da testemunha mergulhada apenas em água destilada. Em seguida, as larvas foram expostas ao parasitismo de D. longicaud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Investigations which tested the oil extracted from the tree Azadirachta indica, showed that when this oil is sprayed on C. capitata larva, it works as repellent for the parasitoid D. longicaudata in different concentrations. However, it neither damaged the C. capitata larva, nor their adults emerged from this situation [35]. In a study which investigated the interaction of D. longicaudata and the toxicity of A. indica extract, it was showed that such bioinsecticide had a negative effect over the emergency of C. capitata adults, but also the same results for the natural enemies [36].…”
Section: Discussionmentioning
confidence: 94%
“…Investigations which tested the oil extracted from the tree Azadirachta indica, showed that when this oil is sprayed on C. capitata larva, it works as repellent for the parasitoid D. longicaudata in different concentrations. However, it neither damaged the C. capitata larva, nor their adults emerged from this situation [35]. In a study which investigated the interaction of D. longicaudata and the toxicity of A. indica extract, it was showed that such bioinsecticide had a negative effect over the emergency of C. capitata adults, but also the same results for the natural enemies [36].…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, the effect of NSC on C. capitata is enhanced by the extended period of exposure beginning in the larval third instar and lasting until adult emergence. França et al (2010) found that an increase in medfly emergence at higher concentrations of neem was related to the repellent effect of neem to the parasitoids when larvae were treated with neem (oil) before exposure to parasitoids. As a result, the reduced parasitism rate of larvae exposed to the highest concentrations of neem favored the development of fruit fly larvae.…”
Section: Discussionmentioning
confidence: 98%